Analisis Fenimisme Liberal Pada Dampak Pernikahan Usia Dini - Adeline Pastika Muham; Adinda Salwa Azahra Sani; Anisah Mufidah Pulungan; Fadillah Melani Putri; Mytha Alvia Rosha Manurung; Paiman Nadeak; Fazli Rachman (Public Service and Governance Journal, 2024)
Early marriage is a social phenomenon that involves marriage at a very young age, often before reaching adulthood or the legal age for marriage. This practice has a significant impact on children's rights, well-being and gender equality around the world. This article explains the phenomenon of early marriage, including the causes, impacts, and efforts to overcome this problem. The causes of early marriage vary, including cultural, religious, economic and social factors. Early marriage is often linked to gender inequality, social pressure and poverty. The impacts of early marriage include higher health risks, interrupted education, and increased risk of domestic violence, especially among girls. Efforts have been made globally to reduce early marriage through legislation, education, and awareness. Laws and regulations have been introduced to set a minimum age for marriage, while education and outreach programs aim to change society's views regarding this practice. While there has been progress in addressing the issue of early marriage, complex challenges remain, and cross-sector collaboration remains key to achieving positive change. Early marriage is an issue that requires serious attention from society, government and non-governmental organizations to protect children's rights and promote gender equality